2002
DOI: 10.1152/japplphysiol.01078.2001
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous nitric oxide modulates responses of tissue and airway resistance to vagal stimulation in piglets

Abstract: The role of endogenous nitric oxide (NO) in modulating the excitatory response of distal airways to vagal stimulation is unknown. In decerebrate, ventilated, open-chest piglets aged 3-10 days, lung resistance (RL) was partitioned into tissue resistance (Rti) and airway resistance (Raw) by using alveolar capsules. Changes in RL, Rti, and Raw were evaluated during vagal stimulation at increasing frequency before and after NO synthase blockade with N(omega)-nitro-L-arginine methyl ester (L-NAME). Vagal stimulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
10
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
4
10
0
Order By: Relevance
“…These findings for pulmonary function are consistent with the known role of NO in the regulation of both bronchomotor tone and peripheral contractile elements in the developing lung (40). We were surprised to find no positive association of in vitro surfactant function with parameters of lung function as observed in adult patients with idiopathic pulmonary fibrosis (29).…”
supporting
confidence: 81%
“…These findings for pulmonary function are consistent with the known role of NO in the regulation of both bronchomotor tone and peripheral contractile elements in the developing lung (40). We were surprised to find no positive association of in vitro surfactant function with parameters of lung function as observed in adult patients with idiopathic pulmonary fibrosis (29).…”
supporting
confidence: 81%
“…Moreover, the potent NO synthase (NOS) inhibitor N G -nitro- L -arginine methyl ester ( L -NAME) has been found, as expected, to induce an increase in airway resistance in guinea pigs [7,8] and pigs [9,10], but this finding was not confirmed in rats [11] or in humans [12]. …”
Section: Introductionmentioning
confidence: 99%
“…In the developing lung, NO participates in pulmonary vascularization, alveolarization, and airway branching, and also counteracts apoptosis in multiple lung cell types (3)(4)(5)(6). In the perinatal period, epithelium-derived NO is critically involved in the regulation of lung liquid production and of peripheral contractile elements (7,8), and it also mediates pulmonary vasomotor tone (9). In studies of lungs from fetal baboons, we showed that all three NOS isoforms, neuronal NOS (nNOS), endothelial NOS (eNOS), and inducible NOS (iNOS), are principally expressed in proximal respiratory epithelium, and that there are maturational increases in their abundance and in NO production during the early third trimester (10).…”
mentioning
confidence: 99%